A Society Caught in a Vicious Cycle and People Unable to Love - Wu, Shujie; Mao, Sinuo (International Journal of Social Sciences and Public Administration, 2025)
The dominance of meritocracy-driven, in-volutional competition is reshaping young people’s emotional practices, giving rise to the phenomenon of "inability to love". This study employs a three-dimensional isomorphous analysis framework of "occupational burnout–emotional exhaustion" to reveal three manifestations of this inability among youth: emotional depletion and inability to invest, dehumanisation and the instrumentalisation of romance, alongside low personal accomplishment and crises of self-identity.This paper contends that through mechanisms such as time compression, meritocracy supremacy, and inflated instrumental rationality, the competition of the ’involution’ constrains young people’s emotional investment in marriage and romance, reflecting the paradoxes of modernity within the process of individualisation.